Eksploracyjna analiza przestrzenno-czasowa wydatków publicznych na ochronę zdrowia w wybranych krajach OECD - Strzelecka, Agnieszka (The exploratory space-time analysis the public expenditures on health care in selected OECD countries, 2006)
An interest generated by the proper qualification of tools indirectly used for the creation of health care policy, enables to conduct a deeper analysis of phenomena connected with the field of economy, what is a health care. Taking into account an influence of health care organization and financing systems on generating expenses in existing health care models, the multivariate comparative analysis including specification of individual systems was conducted in the study as well as an attempt to determine short- and long-term tendencies for selected OECD countries was undertaken. The statistical data used in the research concern an “old” European Union and Poland and include the time period of 1990-2002.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 317-325